GLYCAEMIC INDEX OF SELECTED FOODSTUFFS IN HEALTHY PERSONS - Fajkusova, Zuzana; Jadviscokova, Tereza; Pallayova, Maria; Matuskova, Veronika; Luza, Jiri; Kuzmina, Galina (Biomedical papers, 2007)
Aims: The aim of this study was to determine glycaemic index (GI) of 10 popular foodstuffs/mixed meals in healthy persons.Methods: Ten tested foodstuffs and glucose standard were consumed in three replicates in the course of a defined 9-day meal plan: puffed rice squares with chocolate, dark chocolate, white bread, honey and glucose for breakfast (at 7 a.m.) and dinner (at 8 p.m.); pasta with meat, fried fish with mashed potatoes, and buttered apricot dumplings for lunch (at 12 a.m.); wafers, puffed spelt squares with chocolate, and tomato soup for snack (at 4 p.m.). Each portion contained 50 g of carbohydrates and was consumed within 30 minutes. Glucose concentrations were measured by means of the Continous Glucose Monitoring System (CGMS™, Medtronic Minimed, Northridge, CA, USA). The results were processed by Solutions Software (Medtronic Minimed, Northridge, CA, USA) and DegifXL4 software, Palacký University, Olomouc, CZ. Twenty healthy persons aged 21.9 ± 1.39 y (mean ± SE), BMI 23.6 ± 0.63 kg/m2 completed the study.Results: GI of tested foodstuffs ranged from 34.7 % (chocolate) to 105.3 % (puffed rice squares with chocolate). There were more than tenfold differences between minimal and maximal values of the GI for some foodstuffs. Significant interindividual differences were found between GIs of foodstuffs.Conclusions: In twenty healthy persons the glycaemic indexes of ten popular foodstuffs were determined, to be added to the nutritional labels in order to facilitate the optimum meal planning.
Keywords: Nutrition/Glycaemic index/CGMS